The Role of Accessibility and Inclusivity in Instructional Materials in Enhancing Learning for Higher Education Students - Naz, Sumaira; Zafar, Jam Muhammad; Ullah, Naeem (Annals of Human and Social Sciences, 2024)
This study explores the role of accessibility and inclusivity in instructional materials in enhancing learning experiences in higher education. It investigates how instructional materials supports accessible and inclusive environments and identifies barriers hindering these efforts. A descriptive survey design was adopted, using a mixed-method (QUAN-qual) approach with an explanatory sequential design. The sample included 16 department heads, 80 teachers, and 320 students, selected through convenient and random sampling. Data collection tools, including questionnaires and interviews, were validated using expert reviews and tested for reliability with Cronbach’s Alpha. Data were analyzed in SPSS-24 using descriptive statistics and correlation techniques. Most respondents found the university website accessible (mean score = 3.36, SD = 1.36). They also recognized support for students requiring accessible content (mean = 3.37, SD = 1.22). The study recommends that the universities should prioritize the development of accessible instructional and digital materials while providing assistive technologies to address diverse student needs.